Analisis Strategi Komunikasi Dalam Pelaksanaan Pelatihan Penggunaan Aplikasi Grab Merchant Pada Pt. Grab Teknologi Indonesia - Wulantresna, Pratami; Pramesti Dewi, Rd. Dancu Lokita; Prihadini, Diana; Retnosari, Desi (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
In communicating the right strategy is needed so that the purposeof communication can be achieved well. Communication is donewithout the resulting strategy many errors in the actualization ofthe information obtained. Strategy communication is not only theformulation of concepts and implementation, more than thatstrategy communication is carried out in stages with a clear goal. There are 6 stages communication strategy is the source,message, channel, receiver, effect and feedback. As An AnalysisOf Communication Strategies In The Implementation Of Training Use of Grab Merchant application at PT. GrabTechnology Indonesia. Is a training program, the training needsto pay attention to management or management. Management is important so thattraining objectives can be achieved to the maximum. As withmanagement in general, management training programs related tothe activities of the Trident, namely planning, implementation, andevaluation.